Solar cooling integrated facades: Framework for the integration of solar cooling technologies in the building envelope - Prieto Hoces, Alejandro Ignacio; Knaack, Ulrich; Auer, Thomas; Klein, Tillmann (A+BE | Architecture and the Built Environment, 2018)
Solar cooling systems have gained increased attention these last years, for their potential to lower indoor temperatures using renewable energy. However, architectural integration of these systems in buildings has not been fully explored. Current developments such as small scale solar driven heat pumps and solar cooling kits commercially available for application raise questions about how to successfully integrate these systems into buildings, while present interesting opportunities for the development of new performance based façade components or even self-sustaining cooling façade modules for high-performing commercial buildings. So, what are the conceptual issues and state-of-the-art components and systems to consider for solar cooling façade integration? This chapter discusses current possibilities for façade integration of solar cooling systems, generating a framework for the understanding and further development of solar cooling façade systems. The proposed framework was made by means of a review of solar cooling technologies and solar cooling façade concepts reported by several researchers. The outcomes of the chapter are a matrix outlining the possibilities for the integration of several components and subsystems from the entire cooling process (cooling generation, distribution and delivery), and an early assessment of the development level of state-of-the-art experiences within the field considering examples from current research projects and working prototypes, for the development of solar cooling integrated façade concepts.